The Experiences of Primary Healthcare Nurses During Covid-19 pandemic: Voices from Nursing Staff at King Fahad Specialist Hospital in Buraydah - Al-Rasheedi, Khaled Falah; Al-Rasheedi, Nasser Abdullah; Al-Rasheedi, Fayez Shaman; Al-Mansour, Muhammad Saleh; Al-Harbi, Mufleh Ali (Journal of medical and pharmaceutical sciences, 2023)
With the emergence of coronavirus disease (COVID-19), the world has witnessed unprecedented changes in healthcare provision. With the nurses being the most affected healthcare professionals during the pandemic, the current study aimed to examine the experiences of primary healthcare nurses during covid-19 pandemic at King Fahad Specialist Hospital in Buraydah city in the Kingdom of Saudi Arabia. The population of this research consists of all the nurses at King Fahad Specialist Hospital in Buraydah Saudi Arabia whose number is (128) nurses. The target sample included the whole research population using the complete census method. Using the questionnaire as the main data collection tool, the researchers distributed the questionnaire to the target sample and got only (106) complete responses. The duration of the study took about (1) month starting from 01 October 2022 until 02 November 2022. The findings of the study showed that the nurses experienced major employment changes during the pandemic such as extra work hours, the thought of resigning and moving to other clinical areas, and taking long vacations. Also, the findings showed that the nurses experienced major psychological problems such as anxiety, fatigue, and lack of communication, and support from their co-workers and superiors. It has also been reported that the lack of medical suppliers, lack of personal protective equipment, and the extra volume of infected patients served as major challenges experienced by the nurses during the pandemic. The researchers provided a set of recommendations that focused mainly on the importance of organizational intervention and supporting the nurses both psychologically and professionally with an extended focus on training and qualification for the nurses to deal with such crises.
Keywords: Primary Healthcare; Nurses; Covid-19 Pandemic; King Fahad Specialist Hospital in Buraydah; Saudi Arabia